THE INFLUENCE OF PROMOTION, PRODUCT INNOVATION AND SERVICE QUALITY ON CUSTOMER SATISFACTION AT McDONALD’S SLAMET RIYADI SURAKARTA - Sonia Kartika Wulan; Supawi Pawenang; Ratna Damayanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research intined to determine promotion, product innovation and service quality simultaneously or partially on customer satisfaction at McDonald's Slamet Riyadi in Surakarta City. This kind of research is quantitative, with population of all consumers who have purchased and consumed McDonald's at Slamet Riyadi Surakarta City, the sampling technique make use of purposive sampling technique. Sample amount 100 respondents. Methods of data analysis utilize multiple linear regression analysis. Results the show promotion, product innovation and service quality have a simultan and significant effect on customer satisfaction. Whereas in the t test promotion does not have a significant effect on customer satisfaction, product innovation has a positive and significant effect on customer satisfaction, and service quality has a positive and significant effect on customer satisfaction. Keywords: promotion, product innovation, service quality and customer satisfaction